CORRECTION OF EARLY UTERO-PLACENTAL HOMEOSTASIS DISORDERS IN WOMEN WITH THREATENED ABORTION - Игитова, Марина Борисовна; Горбачева, Татьяна Ивановна; Немцева, Галина Викторовна; Мегрелидзе, Елена Викторовна (Mother and Baby in Kuzbass, 2017)
A study of concentrations of stable metabolites of nitric oxide in the blood serum of 82 patients with threatened abortion in the first trimester and 80 women with physiological early gestation was conducted. Stable metabolites of nitric oxide concentrations has been significantly reduced and amounted 9,06 ± 0,31 mcmol/l in women with threatened abortion (in the comparison group – 9,98 ± 0,29 mcmol/l, p = 0,023), that reflecting utero-placental homeostasis disorders in complicated early pregnancy. Stable metabolites of nitric oxide concentrations has an increased to the level of an uncomplicated pregnancy in the progestogen therapy.